Peran Akuntansi Biaya Lingkungan Dalam Mendorong Praktik Perikanan Berkelanjutan - James Pelupessy (P3M Politeknik Negeri Ambon, 2025)
The implementation of environmental cost accounting has the potential to transform the fishing industry in Maluku's perspective on natural resource sustainability and strengthen government and community efforts to protect the marine ecosystems that constitute the region's primary asset.This study used a qualitative approach to evaluate sustainable fishing practices. Environmental costs are not yet recorded or considered in calculating the profitability of fishing businesses, despite the potential for ecosystem damage and operational waste. Operational activities have the potential to damage the environment from high fuel consumption to fishing gear that poses risks to coral reefs.